PEDESTRIAN CROSSINGS AND RULES OF MOVEMENT IN THEM (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Pedestrian crossings are critical elements of urban infrastructure designed to enhance the safety and efficiency of pedestrian movement. This article examines the various types of pedestrian crossings, the rules governing their use, and the impact of these rules on pedestrian and vehicular safety. By analyzing data from multiple urban settings, we aim to identify best practices and suggest improvements for pedestrian crossing regulations. This study also explores the behavioral patterns of pedestrians and drivers, and how they interact with the built environment to affect overall traffic safety